2011
DOI: 10.1007/s11095-011-0473-y
|View full text |Cite
|
Sign up to set email alerts
|

PPARα Is Regulated by miR-21 and miR-27b in Human Liver

Abstract: We found that PPARα in human liver is regulated by miRNAs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
87
3

Year Published

2013
2013
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 119 publications
(97 citation statements)
references
References 32 publications
(27 reference statements)
7
87
3
Order By: Relevance
“…Following the discovery of developmental and sexual CYP3A4 transgene expression in CYP3A4-transgenic mouse models (Yu et al, 2005), we demonstrated the involvement of miR-27b and murine miR-298 (mmu-miR-298) in regulation of CYP3A4 through targeting of its 39UTR as well as the vitamin D receptor transcription factor (Pan et al, 2009a). Other studies also revealed the importance of miR-27b in regulation of P450 enzyme CYP1B1 (Tsuchiya et al, 2006) and nuclear receptors retinoid X receptor alpha and peroxisome proliferator-activated receptor alpha (Ji et al, 2009;Kida et al, 2011). These findings indicate that miRNAs may modulate drug metabolism through "direct" and "indirect" regulation of drug-metabolizing enzymes.…”
Section: Noncoding Micrornas In the Control Of Drug Metabolism And Trmentioning
confidence: 72%
“…Following the discovery of developmental and sexual CYP3A4 transgene expression in CYP3A4-transgenic mouse models (Yu et al, 2005), we demonstrated the involvement of miR-27b and murine miR-298 (mmu-miR-298) in regulation of CYP3A4 through targeting of its 39UTR as well as the vitamin D receptor transcription factor (Pan et al, 2009a). Other studies also revealed the importance of miR-27b in regulation of P450 enzyme CYP1B1 (Tsuchiya et al, 2006) and nuclear receptors retinoid X receptor alpha and peroxisome proliferator-activated receptor alpha (Ji et al, 2009;Kida et al, 2011). These findings indicate that miRNAs may modulate drug metabolism through "direct" and "indirect" regulation of drug-metabolizing enzymes.…”
Section: Noncoding Micrornas In the Control Of Drug Metabolism And Trmentioning
confidence: 72%
“…In addition to direct targeting of CYP3A4 (Pan et al, 2009a), CYP1B1 (Tsuchiya et al, 2006), and ABCB1 (Zhu et al, 2008), miR27b/a was able to act on a number of xenobiotic receptors and transcription factors including NR1I1/ (Pan et al, 2009a), NR1C1/ PPARa (Kida et al, 2011), ERa/NR3A1 (Li et al, 2010a), NFE2L2/ Nrf2 (Narasimhan et al, 2012), and RXRa/NR2B1 (Ji et al, 2009). Therefore, alteration of enzyme/transporter protein outcome by miR27b/a could be an accumulative effect from direct targeting of the enzyme/transporter and "indirect" targeting of regulatory factors including xenobiotic receptors and transcription factors (Yu, 2009;Yu and Pan, 2012).…”
Section: Micrornas In Posttranscriptional Gene Regulationmentioning
confidence: 99%
“…It has been reported that miR-27 enhances differentiation of osteoblasts and strongly inhibits adipogenesis (Lin et al, 2009;Wang and Xu, 2010). MiR-27b is a regulatory hub in lipid metabolism through repressing critical regulators of lipid homeostasis, such as PPARα, HMGCR (Kida et al, 2011, Vickers et al, 2013. In a recent study, miR-27b was reported to specifically target to bovine myostatin (Miretti et al, 2013).…”
Section: Discussionmentioning
confidence: 99%